2016
DOI: 10.1097/sap.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hemifacial Composite Flap Perfusion Assessment Using Spatial Frequency Domain Imaging

Abstract: Background Vascularized composite allotransplantation (VCA) represents an important advancement in the field of reconstructive microsurgery and has continued to increase in popularity. The significant clinical morbidity associated with flap failure represents an important barrier to even more widespread use of these techniques. Early identification of vascular compromise has been associated with a higher salvage rate, yet most surgeons rely only on clinical assessment intraoperatively. Spatial frequency domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Obtaining deeper biopsies and/or obtaining imaging have been proposed as a method to evaluate larger vessels and for the significance of deep inflammatory infiltrates in the absence of visual changes of rejection. In VCA, the use of noninvasive vascular imaging techniques for perfusion is being investigated . The role of noninvasive vascular imaging in monitoring for or evaluating rejection in VCA is undefined, although it may have some promise in other areas of transplantation.…”
Section: Strengths and Limitations Of The 2007 Banff Vca Working Clasmentioning
confidence: 99%
“…Obtaining deeper biopsies and/or obtaining imaging have been proposed as a method to evaluate larger vessels and for the significance of deep inflammatory infiltrates in the absence of visual changes of rejection. In VCA, the use of noninvasive vascular imaging techniques for perfusion is being investigated . The role of noninvasive vascular imaging in monitoring for or evaluating rejection in VCA is undefined, although it may have some promise in other areas of transplantation.…”
Section: Strengths and Limitations Of The 2007 Banff Vca Working Clasmentioning
confidence: 99%
“…Multiple groups have demonstrated the feasibility of SFDI to measure ischemic onset in a number of organs: including skin flaps, 14,101-104 kidney, 105 bowel, 14 liver, 14 and facial transplants. 106 These studies have served as benchmarks to establish validity, sensitivity, and clinical relevance of SFDI oxygenation and hemoglobin measurements. It was first demonstrated in 2011 that oxygenation measurements trends using SFDI during an occlusion matched trends measured by FDAcleared oximeter devices.…”
Section: Surgical Guidancementioning
confidence: 99%
“…101 Beyond the diagnostic potential of oxygenation imaging, it was also demonstrated that the source of the occlusion (arterial versus venous) could be identified as early as 2 min after blockage in a hemifacial composite flap transplants. 106 Published clinical data using SFDI have been limited. A first-in-human pilot study involving three patients established the capability of SFDI to work under the constraint of flap transplantation surgeries.…”
Section: Surgical Guidancementioning
confidence: 99%
“…[1][2][3][4][5][6] Some medical fields in particular, such as surgery, are driving this need for realtime interpretable information content to aid decision-making in a time-constrained environment. [7][8][9][10][11][12] Several solutions have been investigated to fulfill this need, each with their pros and cons, ranging from raster scanning of microscopic information to wide-field acquisitions of diffused information. 13,14 For instance, fluorescence imaging to help surgeons visualizing structures of interest, such as lymph nodes, ureters, or micrometastasis, stands as an example where providing tissue-related information in real time plays a key role in clinical adoption.…”
Section: Introductionmentioning
confidence: 99%